The impact of interventions by pharmacists collected in a computerised physician order entry context: a prospective observational study with a 10-year reassessment (Swiss Medical Weekly, 2019)
AIMS OF THE STUDY This study assesses clinical interventions by pharmacists prospectively collected from medical and surgical wards, notably the acceptance of interventions, computerised physician order entry (CPOE)related problems, the potential impact of interventions on patient safety evaluated by a multidisciplinary committee, and their evolution over the 10 years since a first assessment. METHODS A prospective observational study covering 13 months was conducted in a French teaching hospital with a patient information system that integrates an electronic health record (EHR) with a CPOE. Interventions by pharmacists were prospectively recorded using CPOE. All interventions were reviewed by two pharmacists. We assessed the interventions, the possible implications of the CPOE in prescribing errors, and the acceptance of interventions by physicians. A committee reviewed the potential clinical impact for patients. The results were compared with the same outcomes collected 10 years ago in the same hospital. RESULTS A total of 2141 interventions by pharmacists were reviewed. Among them, 1589 (74.1%) were accepted by physicians. Regarding the potential clinical impact, a total of 1136 (53%) interventions concerned prescriptions that were potentially significant or serious for patients and 42 (2%) of them were potentially life-threatening. Ten years earlier, the acceptance rate was 23%. Moreover, 14.7% of errors were attributed to the use of the software, whereas 10 years earlier the rate of errors was 49%. CONCLUSIONS The acceptance rate and frequency of CPOE-related errors were better than 10 years before, which is encouraging and shows the importance of regular training and collaboration with healthcare givers to reduce errors. The routine analysis of interventions by pharmacists with medical staff feedback should continue to improve their relevance and effectiveness.